2004
DOI: 10.1128/aem.70.4.1999-2012.2004
|View full text |Cite|
|
Sign up to set email alerts
|

Evolution of the Core Genome of Pseudomonassyringae , a Highly Clonal, Endemic PlantPathogen

Abstract: Pseudomonas syringae is a common foliar bacterium responsible for many important plant diseases. We studied the population structure and dynamics of the core genome of P. syringae via multilocus sequencing typing (MLST) of 60 strains, representing 21 pathovars and 2 nonpathogens, isolated from a variety of plant hosts. Seven housekeeping genes, dispersed around the P. syringae genome, were sequenced to obtain 400 to 500 nucleotides per gene. Forty unique sequence types were identified, with most strains fallin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

21
239
2
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 405 publications
(263 citation statements)
references
References 58 publications
21
239
2
1
Order By: Relevance
“…S1a) and genetic distances among the strains (Table S7). A genetic distance between concatenated sequences of less than 5% defined clearly the seven previously described phylogroups: phylogroups 1, 2 and 3 [29], phylogroup 4 [15], phylogroup 5 [16] and phylogroups 6 and 7 [4]. We used the same distance threshold of 5% for the delimitations of additional phylogroups (Table S7, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…S1a) and genetic distances among the strains (Table S7). A genetic distance between concatenated sequences of less than 5% defined clearly the seven previously described phylogroups: phylogroups 1, 2 and 3 [29], phylogroup 4 [15], phylogroup 5 [16] and phylogroups 6 and 7 [4]. We used the same distance threshold of 5% for the delimitations of additional phylogroups (Table S7, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…syringae strains isolated worldwide from ∼40 plant hosts. All 96 strains were phylogenetically characterized via multilocus sequence typing (MLST) [40] of the core genome to determine their clonal evolutionary relationships. Both Southern hybridization using T3SE probes and PCR were used to determine the distribution of the HopZ family members.…”
Section: Resultsmentioning
confidence: 99%
“…Forty-two isolates, distributed throughout all five P. syringae phylogroups [40], were positive for at least one effector (Figure 2). Promoter analysis, RT-PCR, and northern blot analysis (Figure S1) confirmed that a total of 39 isolates from 18 different hosts express hopZ , with 16 strains expressing hopZ1 , 13 expressing hopZ2 , and ten expressing hopZ3 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Establishing different kinds of strain evolution (i.e., diversifying, directional, purifying) is a fundamental prerequisite for better understanding the epidemiology and the cycle of disease of the pathogen [12]. So far, the studies concerning MLST analysis and plant pathogenic bacteria revealed that Xylella fastidiosa, the Pseudomonas syringae complex and the "core" genome of Ralstonia solanacearum have a clonal structure [12][13][14], whereas in the pathogenicity islands, in gyrB and in four other gene fragments of P. viridiflava, in gyrB and rpoD of P. syringae pv. Tomato, as well as in the virulence-related egI and hrpB genes of R. solanacearum, recombination contributed more than mutation to the genetic variability among strains [12,15,16].…”
Section: Introductionmentioning
confidence: 99%